2012
DOI: 10.4137/bcbcr.s10293
|View full text |Cite
|
Sign up to set email alerts
|

Why, after Chemotherapy, is it Necessary to Assess Memory Using Translational Testing?

Abstract: As the number of cancer survivors rises, so does the importance of understanding what happens post-chemotherapy. The evidence is clear that chemotherapy affects not only cancer cells, but also healthy cells including neurons, leading to long-term cognitive dysfunction in a large portion of survivors. In order to understand the mechanism of action and in the hope of reducing the potential neurocognitive side effects of chemotherapy, pre-clinical testing should be used more effectively. However, the field is lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 74 publications
(158 reference statements)
0
16
1
Order By: Relevance
“…9,12 The majority of the US participants report a diminished memory regardless of time postchemotherapy and a reduced way-finding particularly in those with greater than one year postchemotherapy, which is consistent with previous studies. 11,13,39,40 Although fewer PR women report short-term memory loss and way-finding, .20% reported a decline in both. This study was limited in what type of memory loss patients were asked to report; consequently, a difference in reporting of a specific type of memory loss may not represent an actual difference in memory loss overall.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…9,12 The majority of the US participants report a diminished memory regardless of time postchemotherapy and a reduced way-finding particularly in those with greater than one year postchemotherapy, which is consistent with previous studies. 11,13,39,40 Although fewer PR women report short-term memory loss and way-finding, .20% reported a decline in both. This study was limited in what type of memory loss patients were asked to report; consequently, a difference in reporting of a specific type of memory loss may not represent an actual difference in memory loss overall.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with numerous reports of long-term spatial learning and memory impairments reported postchemotherapy. 13 Fewer PR women (34.8%) compared to US women (54.5%) reported that a medical professional discussed the cognitive side effects of chemotherapy with them ( Table 5). The majority (PR 73.9% and US 78.8%) of participants wished that they had received information about how chemotherapy and other medications can affect memory (Table 5), which did not significantly correlate with whether an individual reported an impairment (data not shown).…”
Section: Reported Memory Loss and Awareness Of Side Effectsmentioning
confidence: 99%
See 3 more Smart Citations